The Decline of the aristocracy and second Duke of Westminster 1900-40. - Carter, Nicola Maeve (Trinity College Dublin. School of Histories & Humanities. Discipline of History, 2022)
The title of my thesis is 'The Decline of the aristocracy and second Duke of Westminster 1900-40'. As my subject I have used the second Duke of Westminster to examine how the aristocracy reacted to the social, economic and political challenges to their status during the years 1900-40. The thesis research required the analysis of primary sources including letters, memoirs, newspapers and estate records to form an argument regarding the manner in which the second Duke of Westminster used his wealth, title and status to maintain a position in Society and influence political policies. The second Duke of Westminster was one of the wealthiest peers in Britain, his experiences in the South African War and the First World War shaped his imperialist politics and introduced him to Sir Winston Spencer Churchill. Throughout his life the Duke used his position to influence, fund and protect imperialist policies. Although the Tariff Reform movement and the Defence of India League failed in the short term, the legacy of both movements was indicative of the power that the wealth and influence the Duke had in a time when the aristocracy had lost their veto over Parliament Acts. The thesis also examines the manner in which the Press perceived and reported about the Duke and how his position influenced the reporting regarding his spending habits. The death duties imposed by the People?s Budget affected the Duke and his decision to sell a Gainsborough, the Blue Boy, drew criticism on the State which had failed to protect a masterpiece from leaving the country. The Duke?s status was such that, he used his wealth and power more implicitly to create a legacy of political influence beyond the common perception of him as a philistine playboy, and as such leads to the conclusion that the decline of the aristocracy and the second Duke of Westminster 1900-40 is a more nuanced issue which has no easy answer as to whether there actually was decline.
APPROVED